Determinan Penerimaan Opini Audit Going Concern (GCAO): - Putri, Silvani; Suhartini, Dwi (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to examine the effect of Financial Distress and Prior Opinion on Going-Concern Audit Opinion, with Opinion Shopping as a moderating variable. This research topic is very important to study in analyzing the extent to which financial and non-financial factors affect the continuity of a company's business. This study uses a quantitative method with a total sample of 185 data points from 37 manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2021. The data analysis used is panel data regression software Eviews 12. The research results prove that the acceptance of the going concern audit opinion by manufacturing sector companies was triggered by the high financial distress and receipt of the modified going concern audit opinion in the previous year. In addition, empirical studies prove that opinion shopping is not a moderating variable in relationships between financial distress and prior opinion on the acceptance of the going concern audit opinion. Keywords: Financial Distess, Prior Opinion, Going Concern Audit Opinion, Opinion Shopping